Feasibility Study on Replicating Tree Design Structure in Trusses Subjected to Lateral Loading - Lim Yap, Kian; Mohammed Parvez, Anwar; Jaganathan, Jayaprakash; Elleithy, Wael; Leong Lau, Teck (International Journal of Engineering and Technology, 2018)
This paper explores the question as to whether designs found in nature can assist in improving current design of structures. The objective of replication of nature is to increase strength and durability with further emphasis on reducing material usage. The basis of this investigation starts with frame structure in the shape of the slope of a tree stump. The study focusses on the effectiveness of various truss design and how it compares to the design found in nature. Although the tree design was found to be no better than the existing frame structures (in terms of rigidity), it still may be potential in other application. In comparison to conventional truss design, the design following tree stump demonstrates a higher flexibility that may prove to be potentially beneficial in resisting lateral load resulting from wind or earthquake.Â Â